2003
DOI: 10.1111/j.1365-2915.2003.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assays for repellents and deterrents for ticks: differing effects of products when tested with attractant or arrestment stimuli

Abstract: Abstract. Most in vivo and in vitro tests with repellents or deterrents against ticks have not considered which sensory channel is being targeted. We have recorded the responses of two hard tick species (Acari: Ixodidae) in vitro to determine if such products can disrupt the perception of an attractant in a repellent assay or the perception of an arrestment stimulus in a deterrent assay. Ethyl butylacetylaminopropionate (EBAAP), N,N-diethyl-methyl-benzamide (deet), permethrin and indalone were chosen to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…Salafsky et al (2000) observed only partial repellency of A. americanum adults using commercial 20% DEET formulations and no protection against Dermacentor variabilis Say. The compound did not repel Amblyomma variegatum Fabricius adults when released with an attractant stimulus (MCMAHON et al, 2003). Based on the results of the present study and on the literature it is clear that A. cajennense is more sensitive to DEET than other tick species so far evaluated.…”
Section: Discussionsupporting
confidence: 53%
“…Salafsky et al (2000) observed only partial repellency of A. americanum adults using commercial 20% DEET formulations and no protection against Dermacentor variabilis Say. The compound did not repel Amblyomma variegatum Fabricius adults when released with an attractant stimulus (MCMAHON et al, 2003). Based on the results of the present study and on the literature it is clear that A. cajennense is more sensitive to DEET than other tick species so far evaluated.…”
Section: Discussionsupporting
confidence: 53%
“…The results observed in the Petri-dish assays may have been due to deterrence, but were also possibly due to the repellent properties of the compounds tested (Ferreira et al, 2001;McMahon et al, 2003). On the other hand, in the olfactometer, arthropods are guided by anaemotactic stimuli, directly influenced by the presence of chemicals in the vapour phase (Ferreira et al, 2001;McMahon et al, 2003;Vilela and Lucia, 2001), thus confirming the repellent property of the compounds.…”
Section: And Human Beings In Relationmentioning
confidence: 52%
“…On the other hand, in the olfactometer, arthropods are guided by anaemotactic stimuli, directly influenced by the presence of chemicals in the vapour phase (Ferreira et al, 2001;McMahon et al, 2003;Vilela and Lucia, 2001), thus confirming the repellent property of the compounds. It is noteworthy that the percentage of repellency observed in the Y-tube olfactometer using the 2-hexanone:benzaldehyde mixture was similar to that observed by Louly et al (2010) when testing crude beagle extracts.…”
Section: And Human Beings In Relationmentioning
confidence: 98%
“…Similarly Dautel et al (1999) reported that I. ricinus nymphs would not contact DEET-treated filter paper. McMahon et al (2003) reported that indalone in an airstream caused A. variegatum to walk downwind, however airborne DEET did not repel ticks attracted to the AAA pheromone. Permethrin, while a toxicant, also repels a range of tick species and is used for treatment of military uniforms (Mehlhorn et al 2003, McCain and Leach 2007, Schreck et al 1995.…”
Section: Repellentsmentioning
confidence: 99%